EVEKTIFITAS PENGENDALIAN KUALITAS AIR UNTUK MENCEGAH PENYAKIT PADA IKAN KOI (CYPRINUS RUBROFUSCUS) DI FARM KOIKITA LOMBOK: Effectiveness Of Water Quality Control To Prevent Diseases In Koi Fish (Cyprinus rubrofuscus) at Farm Koikita Lombok - M.Windi Sugita; Aminullah Aminullah (Yayasan Al-Amin Qalbu, 2026)
The purpose of this study was to describe the effectiveness of water quality control to prevent disease in koi at Koikita Lombok Farm. The study was conducted from October 13 to November 20, 2025, at Koikita Lombok Farm. This quasi-experimental study used observation, interviews, and documentation as data collection techniques. The experiment focused on water quality control to prevent disease in koi at Koikita Lombok Farm. Parameters measured included temperature, pH, and DO. Water quality control to prevent koi disease includes pond cleaning, filtration, installation of filters at the inlet, and control of temperature, pH, and DO. These measures have been shown to help prevent diseases such as Lernaeasis and goiter in koi fry. Koikita Lombok Farm has implemented several basic biosecurity measures, although they have not yet conducted comprehensive water parameter measurements due to limited equipment. Overall, water quality control has increased koi survival by 92%.